Efficiency Performances of Two MPPT Algorithms for PV System With Different Solar Panels Irradiancess - Ali Abdulwahhab Abdulrazzaq; Adnan Hussein Ali (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
A main source of current renewable energy is solar energy. This source of renewable energy can be converted to electrical energy using solar photovoltaic (PV) cells. The Maximum Power Point Tracking (MPPT) earns for maximum energy extractor from PV panels by different irradiance levels. In this paper, overall efficiency of most two popular MPPT techniques utilized in PV applications are analyzed, these  algorithms are Perturb and Observe (P&O) and Incremental Conductance (INC). An analysis of the results for the algorithms based on MATLAB simulation for various changes in solar irradiance is performed. Results showed that the efficiency of P&O algorithm was higher than that of the INC, but to obtain the same performance for both, more concentrated calculations should be used for INC. In measuring the output power, current and voltage responses, the use of a solar array having constant and variable irradiations was employed as input for the algorithms. The output waveforms which were derived from a simulation run for the purpose of obtaining the algorithms response to changes in solar array irradiations were compared. In general, the consequences of the P&O algorithm are quiet good and adequate. However, there is a need to improve the algorithm so as to satisfy the requirements of face confident timing in addition to its rapid response so as to make its performance better than that of InCond algorithms.